Almoravids, Architecture. - Marcos-Cobaleda, María (Brill, 2022)
Almoravid architecture of the Iberian Peninsula and North Africa was an important vehicle for communicating the ideas of the Almoravids (al-Murabitun, r. 454–541/1062–1147), including Maliki orthodoxy, political supremacy over the Almohads (al-Muwahhidun, r. 524–668/ 1130–1269) during the decades when both movements coexisted, and loyalty to the 'Abbasid caliphs of Baghdad (r. 132– 656/750–1258).
https://brill.com/page/510299?srsltid=AfmBOopvw8QRz0u57ENO8Au4f-HbKbBlKftPy10sh9htev47wJ61z-Qr
Keywords: Almorávides; Arquitectura islámica; Almoravids; Architecture